Synthesis Of MnO2 For Surface Modified Electrodes For Heavy Metal Sensors - Derrick Chew, Hsien Nam (Universiti Sains Malaysia, 2022)
In modern times, heavy metal pollution of water sources has become a huge problem due to ongoing human activities such as industrial, mining and agricultural activities. While detection of heavy metals can be done using spectroscopic means, they are unsuitable for real time monitoring of heavy metals due to requirement for expensive equipment, experienced operators and lengthy testing procedures. Electrochemical sensors do not have these problems. However, the electrodes used, such as ITO electrode lacks the sensitivity to detect low concentration of heavy metals. This work investigates the surface modification of bare ITO electrodes with α-MnO2 nanorods to increase the sensitivity and selectivity of bare ITO electrodes for heavy metal detection. α-MnO2 nanorods were synthesized with low temperature hydrothermal method, which is then suspended in ethanol and drop casted on the bare ITO surface, followed by heat treatment and then coating with nafion solution to fabricate Nafion/α-MnO2NR/ITO electrode. Cyclic voltammetry was applied to optimize the concentration of α-MnO2NR suspension and nafion concentration used, where the optimal parameters were found to be 10 mg/ml α-MnO2NR suspension and 0.1% nafion solution. The calculated Limit of Detection (LOD) for Pb(II) for the 0.1%Nafion/α-MnO2NR/ITO modified electrode is 0.393 ppb. Simultaneous stripping analysis of Pb2+, Cd2+ and Cu2+ yields no peaks, however it is likely to be due to poor reproducibility of the electrode. From the interference study of 0.1%Nafion/α-MnO2NR/ITO modified electrode, it is showed that electrode has sufficiently high 4 selectivity for Pb2+, Cd2+ and Cu2+ ions, as these are the only peaks observed out of the 23 different ions presence in the solution.